2019
DOI: 10.1108/ijccsm-09-2017-0177
|View full text |Cite
|
Sign up to set email alerts
|

Climate-entrepreneurship in response to climate change

Abstract: Purpose This study aims to explore South Korean firms’ reactions to climate change issues and the Korean emissions trading scheme (ETS) from the perspective of proactive climate-entrepreneurship. Differences in attitude toward the Korean ETS, implementation of carbon management practices and performance regarding operations, market and emission reductions are also investigated. Design/methodology/approach A research model was developed to investigate the differences in corporate perception of climate change.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, in recent years, it has been revealed that entrepreneurs cannot be limited to only the economic field and may also have purposes other than economic ones. It is reported that entrepreneurs have started to demonstrate that they have goals to protect the ecosystem, take actions against climate change, prevent environmental pollution, not pollute drinking water, and protect biological diversity [14]. In addition, many new entrepreneurs develop business models that aim to cope with the social challenges of the SDGs [15].…”
Section: Literature Review 21 From Classical To Sustainable Entrepren...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, it has been revealed that entrepreneurs cannot be limited to only the economic field and may also have purposes other than economic ones. It is reported that entrepreneurs have started to demonstrate that they have goals to protect the ecosystem, take actions against climate change, prevent environmental pollution, not pollute drinking water, and protect biological diversity [14]. In addition, many new entrepreneurs develop business models that aim to cope with the social challenges of the SDGs [15].…”
Section: Literature Review 21 From Classical To Sustainable Entrepren...mentioning
confidence: 99%
“…Environmental entrepreneurship [16,17] Eco entrepreneurship [18,19] Climate entrepreneurship [14,20] Biosphere entrepreneurship [21] Policy entrepreneurship [22,23] Institutional entrepreneurship [24,25] Sustainable entrepreneurship [26][27][28][29] In Table 1, it can be seen that the types of entrepreneurship focusing on sustainability are defined under different headings. However, the entrepreneurship types focusing only on the environment and ecosystem do not involve the sustainability of societies or cities.…”
Section: Entrepreneurship Types Studiesmentioning
confidence: 99%
“…It is also of interest for studies focused on the business response to climate change [42]. For instance, Lee and Ahn [43] provide evidence that climate-entrepreneurial proactivity favors a more active approach to tackling climate change issues and facilitates organizational and technological innovation, which in turn leads to operational, market, and emission reduction performance. Second, from the perspective of strategic human resource management, employees are perceived as a strategic element in the organization that facilitates the acquisition and maintenance of competitive benefits and consequently, the achievement of organizational goals.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Companies have adopted different strategies to address climate change issues, ranging from “green-washing” to truly transformative circular economy (CE) and social enterprise tactics. This has led to the rise of climate entrepreneurship, with (Lee and Ahn 2019, p. 237) characterising this as “sensing, seeking and integrating climate change issues in business”. The literature on climate entrepreneurship is burgeoning and encompasses regular forms of entrepreneurship that focus on businesses becoming more eco-aligned, as well as principles and practices related to circular approaches, doughnut economics and social entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%